2017
DOI: 10.3892/ijmm.2017.3326
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition protects against diet-induced gallstone formation through modulation of cholesterol and bile acid homeostasis

Abstract: Gallstone disease is one of the most prevalent and costly gastrointestinal disorders worldwide. Gallstones are formed in the biliary system by cholesterol secretions in bile, which result from excess cholesterol, a deficiency in bile salts or a combination of the two. The present study examined the effects of proteasome inhibition on gallstone formation using the proteasome inhibitors bortezomib (BT) and carfilzomib (CF). C57BL/6J mice were fed a lithogenic diet to generate gallstones and injected with BT or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Studies have shown that CSI was more important than cholesterol levels in cholelithiasis formation (5,20). These findings were attributed to an increase in cholesterol and bile salt deficiency (10), and our results are consistent with those findings. We found that the bile cholesterol levels were lower even in the rabbit groups receiving thyroxine hormones because the bile acid levels were much lower in these groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies have shown that CSI was more important than cholesterol levels in cholelithiasis formation (5,20). These findings were attributed to an increase in cholesterol and bile salt deficiency (10), and our results are consistent with those findings. We found that the bile cholesterol levels were lower even in the rabbit groups receiving thyroxine hormones because the bile acid levels were much lower in these groups.…”
Section: Discussionsupporting
confidence: 92%
“…The association between serum lipid levels and gallstone has been reported and studies have shown that cholesterol saturation index (CSI), which is one of the main factors for gallstone formation, was more crucial than cholesterol concentration (8,9). CSI is described as the ratio of measured concentration of cholesterol to the measured concentration of bile salts plus phospholipid (10). A gallstone starts with a nucleus formation, and it has been shown that nucleus formation time was shortened by a lithogenic diet (4,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol homeostasis is very important for broilers, as its metabolism dysfunction will lead to atherosclerosis, bile duct blockage or gallstones and other diseases [43,44]. The TC, TG, HDL-c, and LDL-c contents in serum are important indicators of cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP7A1 gene is highly regulated, as might be expected for an enzyme with a central role in the clearance of an important sterol (Guengerich 2015, Zhang, Zhao, et al 2017, Zhang, Jackson, et al 2017, Zhang, Wang, et al 2018, Lee et al 2018). Transcription of the CYP7A1 gene is stimulated by dietary cholesterol in rodents (Horton et al 1995).…”
Section: P450 7a1mentioning
confidence: 99%